May laro ang diskurso ng katarungan - Rodriguez, Agustin Martin G.; Ateneo de Manila University Press (Quezon City Ateneo de Manila University Press, 2014)
On philosophy of social sciences.
Includes bibliographical references (pages 250-253) and index.
Keywords: Social sciences -- Philosophy